A Revealed Preference Approach to Understanding Corporate Governance Problems: Evidence from Canada - Robert S. Chirinko; Huntley Schaller (Center for Economic Studies and ifo Institute (CESifo), 2002)
By studying the gap between the discount rates used by executives and shareholders, we assess the extent to which governance problems distort firm behavior. The estimation strategy recovers discount rates used by executives from the pattern of their actual investment spending. Our empirical work is based on panel data for 193 Canadian firms. For the firms most likely to be affected by Free Cash Flow agency problems, investment behavior appears to be guided by discount rates that are less than the market rate by 350-400 basis points. This wedge is reduced for firms with a concentrated ownership structure. Firms in our sample facing Free Cash Flow problems have a stock of fixed capital approximately 7 per cent to 22 per cent higher than would prevail under value maximizing behavior.
Keywords: E20; G30; 330; corporate governance; business investment; discount rates